2022
DOI: 10.1001/jamaoncol.2021.5784
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Telemedicine Use Among US Patients With Newly Diagnosed Cancer by Socioeconomic Status

Abstract: The lowest socioeconomic status (SES) quartile is SES 1, and SES 4 is the highest quartile. Error bars represent the 95% Wilson score CIs for the proportions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
27
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 5 publications
5
27
0
Order By: Relevance
“…A recent analysis of claims data from a large commercial insurer examined patients with newly diagnosed cancer at the start of the pandemic. This study showed that patients in the highest quartile of a socioeconomic index were 31% more likely to utilize telemedicine when compared with those in the lowest quartile 41 . Although telemedicine is a novel potential pathway for accessing cancer care, it is not universally accessible, and patient factors such as literacy, familiarity with technology, or access to resources such as mobile devices and wireless connections may represent barriers to telemedicine access in disadvantaged populations 42 .…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…A recent analysis of claims data from a large commercial insurer examined patients with newly diagnosed cancer at the start of the pandemic. This study showed that patients in the highest quartile of a socioeconomic index were 31% more likely to utilize telemedicine when compared with those in the lowest quartile 41 . Although telemedicine is a novel potential pathway for accessing cancer care, it is not universally accessible, and patient factors such as literacy, familiarity with technology, or access to resources such as mobile devices and wireless connections may represent barriers to telemedicine access in disadvantaged populations 42 .…”
Section: Discussionmentioning
confidence: 78%
“…This study showed that patients in the highest quartile of a socioeconomic index were 31% more likely to utilize telemedicine when compared with those in the lowest quartile. 41 Although telemedicine is a novel potential pathway for accessing cancer care, it is not universally accessible, and patient factors such as literacy, familiarity with technology, or access to resources such as mobile devices and wireless connections may represent barriers to telemedicine access in disadvantaged populations. 42 Our finding that 43% of the variation in telemedicine use patterns was driven by the physicians also emphasizes the importance of engaging providers, care teams, and health systems in understanding and directly addressing potential inequities in telemedicine access.…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review showed that rural cancer survivors significantly valued digital approaches to the management of their care [38]. This coupled with the ubiquity of smartphone devices and significant apprehension about the adverse consequences of disruptions or delays in cancer care may have motivated pandemic-related use of telemedicine among patients with cancer [39]. However, as others have highlighted, understanding the role of digital health strategies in the organization and delivery of rural cancer care is a significant gap in the literature [38].…”
Section: Discussionmentioning
confidence: 99%
“…Patient level medical comorbidities were included as patients with a higher degree of comorbidities may have a differential utilization of telemedicine services. Area level measures of socioeconomic status and rurality were included, as previous studies suggest that these factors may influence telemedicine access and utilization [ 16 , 17 ]. In a secondary, exploratory analysis, limited to patients who had at least one telemedicine encounter during the study period, the primary logistic regression model was refit with at least one video telemedicine (vs. no video telemedicine) as the outcome of interest.…”
Section: Methodsmentioning
confidence: 99%